Assessment of Occupational Risk in the Case of the Ultrasonic Noise Exposure - PLEBAN, Dariusz; SMAGOWSKA, Bożena; RADOSZ, Jan (Archives of Acoustics, 2021)
Increased efficiency of production and improved quality have contributed to the development of ultrasonic technological applications, in which low frequency ultrasounds are generated to operate, accelerate as well as to facilitate technological processes. Technological ultrasonic devices (i.e. sources of ultrasonic noise in the work environment, e.g. ultrasonic washers, ultrasonic welding machines) have relatively high power and their nominal frequencies are in the range from 18 kHz to 40 kHz. In Poland, ultrasonic noise (defined as noise containing high audible and low ultrasonic frequencies from 10 kHz to 40 kHz) is included in the list of factors harmful to health in the work environment and therefore the admissible values of ultrasonic noise in the workplaces are established. The admissible values of ultrasonic noise and the new ultrasonic noise measurement method make it possible to perform the assessment of occupational risk related to ultrasonic noise. According to this method, the scope of the measurements includes the determination of the equivalent sound pressure levels in the 1/3 octave bands with the centre frequencies from 10 kHz to 40 kHz. This paper presents the description of both, i.e. the method for ultrasonic noise measurements and the method of the assessment of occupational risk related to ultrasonic noise. The examples of the results of the assessment of occupational risk related to exposure to ultrasonic noise are also discussed.